A multi-scale moisture diffusion coupled with stress model for composite materials. (1st July 2017) - Wang, Jingze; Dai, Fuhong; Ma, Li
Abstract: In this paper, an equivalent model on coefficient of hygrothermal expansion for composite layer and a multi-scale model for calculating the strain and stress of composite plates are proposed. These two models also can be applied to thermal expansion problems and guide the structure design of the composite materials. A model descripting the coupling behavior of moisture diffusion and stress in composite laminates is proposed based on the second Fick's law. Compared to other models, this model can accurately predict the anomalous behavior in the process of moisture absorption. A number of experiments and finite-element simulations are conducted to validate this model. A comparison of the model's predictions with experimental data shows a good agreement.